Implementation of educational policies for migrants: A case study in the Swiss canton of Geneva - Fouquet-Chauprade, Barbara; Napoli, Julia (Education Policy Analysis Archives, 2021)
The Swiss context presents a specific pattern being a confederal country relying on a subsidiarity principle. Thus, the cantons operate in a framework of a reduced power of central authority (Boulenger et al., 2012; Revaz, 2020) and are autonomous regarding education policies at local level (Akkari, 2019). However, since the adoption of a new law in 2005, the Federal Council, cantons, municipalities and cities officially collaborate on migration policy (Chifelle, 2018; Facchinetti, 2012). In this particular context, the confederation developed migration policies giving guidance to cantonal governments. Our research aimed at analyzing a confederal policy guidance on migrants’ education and its interpretation in the canton of Geneva. In particular, we examined the ”decoupling” between general guidance from the Confederation and the implementation at local level. For this purpose, we studied the implementation of a cantonal program named L’école des mamans (mothers’ school) dedicated to prepare migrants’ families for their children enrolment in primary school. Our main results show that there is a distortion between policy objectives and the implementation phase. We also observe a model of resistance to change with no modification of actors’ practices towards migrants’ parents despite the new integration policy guidance.